THE EFFECTS OF ACUTE BEER INGESTION ON RECOVERY OF NONLINEAR HEART RATE VARIABILITY AFTER EXERCISE: a RANDOMIZED, CROSSOVER AND CONTROLLED TRIAL - Pontes, Yasmim M. de Moraes; Benjamim, Cicero Jonas R.; Liberalino, Gabriela Augusto; Porto, Andrey A. [UNESP]; Garner, David M. [UNESP]; Valenti, Vitor E. [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2022)
Objective: We estimated the acute effects of acute beer consumption on non-linear HR Variability (HRV) behavior after submaximal aerobic exercise. Equipment and methods: This is a transversal, crossover, randomized and controlled trial. Fifteen healthy female and 17 healthy male adults were included in the final sample. Subjects performed two protocols on two randomized days: Water (300 mL) and Beer (300ml). The subjects underwent 15 minutes seated at rest, followed by aerobic exercise on a treadmill (five minutes at 50-55% of maximum HR and 25 minutes 60-65% of maximum HR) and then remained seated for 60 minutes during recovery from the exercise. Water or beer was consumed between four and ten minutes after exercise cessation. Results: The symbolic analysis (0V% and 2LV%), the fractal analysis by Detrended Fluctuation Analysis and the Sample Entropy demonstrated a late recovery in males in the beer protocol. In the women's group, the results were contradictory among the HR fragmentation analysis indexes. Beer consumption by males after a submaximal aerobic test was able to delay recovery of non-linear HRV behavior.
Keywords: Beer; Autonomic Nervous System; Cardiovascular System; Exercise; Heart Rate; Variability